The Regulatory Mechanisms of Tumor Suppressor P16(INK4A) and Relevance to Cancer - Li, Junan (2011)
P16(INK4A) (also known as P16 and MTS1), a protein consisting exclusively of four ankyrin repeats, is recognized as a tumor suppressor mainly due to the prevalence of genetic inactivation of the p16(INK4A) (or CDKN2A) gene in virtually all types of human cancers. However, it has also been shown that elevated expression (up-regulation) of P16 is involved in cellular senescence, aging, and cancer progression, indicating that the regulation of P16 is critical for its function. Here, we discuss the regulatory mechanisms of P16 function at the DNA level, the transcription level, and the posttranscriptional level, as well as their implications in the structure-function relationship of P16 and in human cancers.